STUDI PEMILIHAN JALAN LINGKAR LUAR UTARA YOGYAKARTA - Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2021)
Inter urban traffics through cities cause an additional traffic load within cities. Likewise with the city of Yogyakarta, which is a student city, although now there is a ring road, traffic congestion in the city still have a crucial problem. Therefore, an additional outer ring road is needed to overcome this. One of them is the northern ring road of Yogyakarta with 3 alternative choices and finally option 2 which connects from Prambanan to Tempel, Sleman and ends at Kulon Progo is the best alternative. From the results of the economic study, it gives an Economic Internal Rate of Return value of 21.11% which exceeds the annual interest rate of 12% so it is said to be very feasible to build. The length of the northern outer ring road is 40.6 km with a travel time of 50.9 minutes.. Keywords: outer ringroad, feasible, congestion., EIRR